The Prevalence and Association of Exercise Test Abnormalities With Sudden Cardiac Death and Transplant-Free Survival in Childhood Hypertrophic Cardiomyopathy. Issue 9 (6th November 2022) - Conway, Jennifer; Min, Sandar; Villa, Chet; Weintraub, Robert G.; Nakano, Stephanie; Godown, Justin; Tatangelo, Mark; Armstrong, Kathryn; Richmond, Marc; Kaufman, Beth; Lal, Ashwin K.; Balaji, Seshadri; et al.
Abstract : Background: Hypertrophic cardiomyopathy (HCM) can be associated with an abnormal exercise response. In adults with HCM, abnormal results on exercise stress testing are predictive of heart failure outcomes. Our goal was to determine whether an abnormal exercise response is associated with adverse outcomes in pediatric patients with HCM. Methods: In an international cohort study including 20 centers, phenotype-positive patients with primary HCM who were <18 years of age at diagnosis were included. Abnormal exercise response was defined as a blunted blood pressure response and new or worsened ST- or T-wave segment changes or complex ventricular ectopy. Sudden cardiac death (SCD) events were defined as a composite of SCD and aborted sudden cardiac arrest. Using Kaplan-Meier survival, competing outcomes, and Cox regression analyses, we analyzed the association of abnormal exercise test results with transplant and SCD event-free survival. Results: Of 724 eligible patients, 630 underwent at least 1 exercise test. There were no major differences in clinical characteristics between those with or without an exercise test. The median age at exercise testing was 13.8 years (interquartile range, 4.7 years); 78% were male and 39% were receiving beta-blockers. A total of 175 (28%) had abnormal test results. Patients with abnormal test results had more severe septal hypertrophy, higher left atrial diameter z scores, higher resting left ventricular outflow tract gradient, and higher frequency of myectomy compared with participants with normal test results ( P <0.05). Compared with normal test results, abnormal test results were independently associated with lower 5-year transplant-free survival (97% versus 88%, respectively; P =0.005). Patients with exercise-induced ischemia were most likely to experience all-cause death or transplant (hazard ratio, 4.86 [95% CI, 1.69–13.99]), followed by those with an abnormal blood pressure response (hazard ratio, 3.19 [95% CI, 1.32–7.71]). Exercise-induced ischemia was also independently associated with lower SCD event-free survival (hazard ratio, 3.32 [95% CI, 1.27–8.70]). Exercise-induced ectopy was not associated with survival. Conclusions: Exercise abnormalities are common in childhood HCM. An abnormal exercise test result was independently associated with lower transplant-free survival, especially in those with an ischemic or abnormal blood pressure response with exercise. Exercise-induced ischemia was also independently associated with SCD events. These findings argue for routine exercise testing in childhood HCM as part of ongoing risk assessment.